Design of an automatic cost-effective cracker dryer as an effort to increase the production of squid crackers at Banyuwangi Regency - raafi'u, Brian; Iskandarianto, Fitri Adi; Susilo, Joko; Septyaningrum, Erna; Amrinsyah, Rakmad; Alam, Badrul; Agasta, Tedy (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2024)
Banyuwangi is a regency with a coastline length of about 175.8 km with 10 islands. The east coast of Banyuwangi (Bali Strait) is one of the largest fish producers in East Java. Banyuwangi is the second largest producer of fishery commodities in Indonesia. One of the villages in Banyuwangi Regency, Mojopanggung Village, has the potential for a thriving squid cracker business. The management of crackers in this village has not changed significantly from year to year, 90% of the management of the ponds is done traditionally, starting from the process of making raw materials for crackers, drying crackers to the marketing process. The most common problem faced by cracker business owners is the loss caused by the rainy season. Almost 50% to 75% of the crackers are not produced in a period of 1 to 4 months due to limited sunlight as a medium for drying crackers. This is evident from the decreasing amount of production. The most influential factor is the heating medium that changes based on natural conditions. Meanwhile, the demand for all types of crackers continues to grow. In its management, one of the dynamic elements that need to be considered is the temperature of the cracker dryer. Some of the physical variables that affect the quality of the drying process are temperature, humidity, and automatic scheduling, and to support the success of the cracker drying process, these parameters really need to be known by SME cracker business owners in Banyuwangi Regency. So the need for a cheap and energy-efficient technology for the drying process of crackers, which can produce good quality crackers, so that cracker-producing SMEs can significantly increase their production without any restrictions on natural conditions.